2011
DOI: 10.1029/2011wr010666
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical controls on runoff generation: Topographically driven hydrologic connectivity, geology, and vegetation

Abstract: [1] Understanding the relative influence of catchment structure (topography and topology), underlying geology, and vegetation on runoff response is key to interpreting catchment hydrology. Hillslope-riparian-stream (HRS) water table connectivity serves as the hydrologic linkage between a catchment's uplands and the channel network and facilitates the transmission of water and solutes to streams. While there has been tremendous interest in the concept of hydrological connectivity to characterize catchments, few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
290
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(311 citation statements)
references
References 87 publications
20
290
1
Order By: Relevance
“…Continuous topographic metrics such as the topographic wetness index (TWI, a surrogate for water accumulation) could represent hydrologic influences on variables relevant for CH 4 fluxes (e.g., redox state, diffusivity of CH 4 and O 2 , and substrate availability). Here, we build on previous research from Tenderfoot Creek Experimental Forest (TCEF) that has demonstrated how topographic metrics can represent landscape structure and its influence on hydrologic processes (Jencso et al, 2009;Jencso and McGlynn, 2011) and carbon cycling (Riveros-Iregui and McGlynn, 2009;Pacific et al, 2010Pacific et al, , 2011. Our objectives were to determine how locally and distally mediated environmental conditions influence CH 4 fluxes, and to estimate the net seasonal CH 4 balance of the upper Stringer Creek watershed.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous topographic metrics such as the topographic wetness index (TWI, a surrogate for water accumulation) could represent hydrologic influences on variables relevant for CH 4 fluxes (e.g., redox state, diffusivity of CH 4 and O 2 , and substrate availability). Here, we build on previous research from Tenderfoot Creek Experimental Forest (TCEF) that has demonstrated how topographic metrics can represent landscape structure and its influence on hydrologic processes (Jencso et al, 2009;Jencso and McGlynn, 2011) and carbon cycling (Riveros-Iregui and McGlynn, 2009;Pacific et al, 2010Pacific et al, , 2011. Our objectives were to determine how locally and distally mediated environmental conditions influence CH 4 fluxes, and to estimate the net seasonal CH 4 balance of the upper Stringer Creek watershed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of watershed topography on hydrological processes often include topics such as specific discharge (Karlsen et al, 2016), spatial baseflow distribution (Shope, 2016), transit time (McGuire and McDonnell, 2006;McGuire et al, 2005), and hydrological connectivity (Jencso and McGlynn, 2011). 65…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, no studies have quantified topographic controls on various flow magnitudes. Nevertheless, the relationship between topography and the mean transit time (McGuire and McDonnell, 2006), temporal specific discharge (Karlsen et al, 2016), and hydrological connectivity (Jencso and McGlynn, 2011) have been investigated. It is no doubt that topography is one 230 of the major contributors to hydrological variations (Price, 2011;Smakhtin, 2001).…”
mentioning
confidence: 99%
“…It is well established that hydrological connectivity exhibits not only temporal but also spatial dynamics and that therefore source areas of flow generation vary over time (e.g. Lehmann et al, 2007;Spence et al, 2010;Jencso and McGlynn, 2011;Ogden et al, 2013). Adapting the spatial resolution of models to the spatial resolution of available observations offers considerable potential to improve the representation of process dynamics across the model domain.…”
Section: Spatial Patternsmentioning
confidence: 99%